Long-term safety and vaccine-induced seropositivity in healthy volunteers from HIV vaccine trials. (1st November 2019) - Durier, Christine; Desaint, Corinne; Lelièvre, Jean-Daniel; Silbermann, Benjamin; Pialoux, Gilles; Cuzin, Lise; Bonnet, Bénédicte; Poizot-Martin, Isabelle; Bouakane, Amel; Paul, Christelle; Grabar, Sophie; Spire, Bruno; et al.
Abstract : Background: The ANRS COV1-COHVAC cohort was a long-term safety cohort of healthy volunteers who received preventive HIV-vaccine candidates in 17 phase I/II clinical trials. Methods: Data collected from the first vaccine candidate administration and annually after inclusion in the cohort included grade 3/4 adverse events and all grade adverse events suggestive of neurological, ophthalmological and immune disorders, self-administered questionnaires on behaviors and HIV ELISA results. Age-and-sex-standardized mortality ratios (SMRs) were calculated with respect to the French population. The cohort was early terminated in 2016 due to the absence of safety signal. Results: Of 496 volunteers, 488 were included: 355 in the 7-year prospective follow-up and 133 in the retrospective data collection only. The total follow-up after the first vaccination was 4934 person-years (median: 10 years) and 270 (76%) volunteers completed their follow-up. No relevant adverse event possibly related to the vaccine was reported. Breast cancer incidence and woman mortality did not differ from those of the French general population (standardized incidence ratio = 1.47, P = 0.45 and SMR = 0.65, P = 0.28, respectively) while man mortality was significantly lower (SMR = 0.26, P = 0.0003). At the last visit, 21/29 (72%) volunteers who received the recombinant HIV gp160 protein still showed vaccine-induced seropositivity after a median follow-up of 23 years. Only a few volunteers reported risky sexual practices (men: 20/192, women: 2/162). Conclusion: Volunteers showed a sustained high commitment. No long-term safety alert was identified during the postvaccine follow-up. Participating in vaccine trials did not increase risky behaviors for HIV infection. Vaccine-induced seropositivity may persist for more than 23 years after receiving rgp160. Abstract : Supplemental Digital Content is available in the text